PENGARUH METODE PROBLEM SOLVING DAN METODE DRILL DI KELAS XI SMK KARTIKA MAKASSAR - jumaeni, jumaeni; Amri, Muhammad (ISTIQRA: Jurnal Hasil Penelitian, 2022)
This research aims to explain the application of problem-solving and drill methods to learning outcomes. The method used is quantitative ex-post factors. This research was conducted on class Islamic religious and character education. Then the application of the problem-solving method and the drill method both positively affect the learning outcomes of Islamic religious education and character in class XI students at SMK Kartika XX-1 Makassar.